2020
DOI: 10.5334/cstp.263
|View full text |Cite
|
Sign up to set email alerts
|

Planning and Executing Scientifically Sound Community Science in a Public-Facing Institution

Abstract: community (citizen) science and crowdsourcing participants (human subjects). These crowdsourced participants provide a diverse sample for collecting taste and genetics data, and typically spend about 30 minutes in the Lab during enrollments. Alternatively, the community scientists invest a much more significant amount of time; they volunteer five hours weekly to train and then to assist in all aspects of the Lab's research, including data collection, DNA extraction, and manuscript preparation. This case study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 23 publications
(25 reference statements)
1
10
0
Order By: Relevance
“…This study was aimed as both a scientific study and a visitor participation experience which engages the participants to "create content" and gather a better understanding of scientific methods 34,54,55 . These results are relevant to the scientific community because they demonstrate (similar to the American Gut Project) that important human microbiome trends can be recovered using a citizen science model, which can be a powerful and cost-effective means for collecting from a large population, and engages the public in science 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was aimed as both a scientific study and a visitor participation experience which engages the participants to "create content" and gather a better understanding of scientific methods 34,54,55 . These results are relevant to the scientific community because they demonstrate (similar to the American Gut Project) that important human microbiome trends can be recovered using a citizen science model, which can be a powerful and cost-effective means for collecting from a large population, and engages the public in science 33 .…”
Section: Discussionmentioning
confidence: 99%
“…We used a crowdsourced, cross-sectional convenience oral microbiome sampling of guests visiting the Denver Museum of Nature & Science in Colorado, USA to gain diverse, community-based data across age ranges, health statuses, and families for people living in an urban center of a Western industrialized country. Methods for the generation of crowdsourced data and utilization of citizen science at the Denver Museum of Nature & Science is outlined in Nuessle et al (2020) 34 . Using this citizen science model, trained volunteer citizen scientists facilitated the collection from guests of buccal swabs for microbiome characterization.…”
mentioning
confidence: 99%
“…It aimed to replicate the well-established findings of a previous study on the topic of supertasting-namely that both the ability to detect the bitter compound propylthiouracil and its perceived strength are due primarily to three variations within the TAS2R38 gene (Bartoshuk, Duffy, & Miller, 1994), and to document guests' level of engagement with the study process and its impact on their understanding of study-related topics. The Bitter Study replicated the genetic findings of Bartoshuk et al (1994) and successfully demonstrated that the community science model could be implemented in a museum and collect quality human subject data from crowdsourced participants (see Garneau et al, 2014;Nuessle et al, 2020). An independent evaluation confirmed that museum guests thoroughly enjoyed their experience as Bitter Study enrollees and advanced their understanding of the relationship between genetics and taste.…”
Section: Introductionmentioning
confidence: 77%
“…Individuals willing to make a more long-term commitment can apply to join the Lab as a volunteer community (citizen) scientist. These community scientists spend approximately four hours every week in the Lab learning how to ethically collect and scientifically analyze human subject data (Nuessle, McNamara, & Garneau, 2020). The purpose of this paper is to report on the guest experience of public participation in scientific research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation